Rivaroxaban versus Warfarin for Prevention of Thromboembolism in Bangladeshi Patients with Non-Valvular Atrial Fibrillation (University Heart Journal, 2020)
Background: The use of Warfarin reduces the rate of ischemic stroke in patients with atrial fibrillation but requires frequent monitoring and dose adjustment. Rivaroxaban, an oral factor Xa inhibitor, may provide more consistent and predictable anticoagulant effects than Warfarin.Methods: In this Open comparison trial, the researchers compared Rivaroxaban (at a daily dose of 20 mg or 15 mg daily in patient with a creatinine clearance of 30-49 ml/min ) with dose adjusted Warfarin (target INR 2.0 to3.0) in 2,846 patients with nonvalvular atrial fibrillation and CHA2DS2-VASc Score 2 or more. The primary efficacy outcome was stroke or systemic embolism and primary safety outcome was major or minor bleeding. This research was designed to determine whether Rivaroxaban have more efficacy and safety than Warfarin for the primary outcomes.Results: Total follow-up period was 6 months. Risk factors and co-morbidities were similar in both groups. Baseline investigations were also similar. Age and sex of both groups were matched. The rate of ischaemic stroke was 1.8% in Rivaroxaban group, as compared with 2.18% in the Warfarin group (p 0.479, nonsignificant). The rate of haemorrhagic stroke was 0.53% in Rivaroxaban group, as compared with 1.36 % in the Warfarin group (p 0.026, significant). Systemic embolism was 0.08% in Rivaroxaban group, as compared with 0.15 % in the Warfarin group (p 0.561, non-significant). The rate of major bleeding was 0.4% in Rivaroxaban group and 0.53 % in the Warfarin group (p 0.361, non-significant). The rate of minor bleeding was 2.10% in Rivaroxaban group, as compared with 2.33% in the Warfarin group (p 0.681, non-significant).Conclusions: Rivaroxaban have similar efficacy and better safety profile than Warfarin in patients with nonvalvular atrial fibrillation in Bangladeshi population.University Heart Journal Vol. 16, No. 2, Jul 2020; 99-105